Engaging an international professional learning community to support underrepresented educators in sports leadership - Sterrett, William L.; Mahmood, Aisha; Magnusen, Mar; Bashir, Ahsan; Sukhera, Sohail; Saeed, M. A.; Khan, Ayaz Muhammad; Ramsey, Brooke; Ramsey, Charles; Boersma, Jess; Abel, Hina; Frey, Meredith (Frontiers in Education, 2024)
This article provides insights from a collaborative grant effort centered on supporting women in sports leadership through the context of a global professional learning community. This grant initiative, called IDEA-SPORT, focused on enhancing the leadership and sports knowledge of girls and other vulnerable and under-served populations in sports-related fields by encouraging leadership and sports collaboration through curricular design and leadership exercises. This article will focus on leveraging an international, bi-directional professional learning community and deliver a collaborative data-informed workshop focused on leadership education for social responsibility.